2022
DOI: 10.3390/molecules27082572
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin and Naringenin against Bisphenol A-Induced Neurotoxicity in Zebrafish Model—Potential Flavonoid Molecules for New Drug Design, Development, and Therapy for Neurological Disorders

Abstract: Bisphenol A (BPA), a well-known xenoestrogen, is commonly utilised in the production of polycarbonate plastics. Based on the existing evidence, BPA is known to induce neurotoxicity and behavioural issues. Flavonoids such as silibinin and naringenin have been shown to have biological activity against a variety of illnesses. The current research evaluates the neuropharmacological effects of silibinin and naringenin in a zebrafish model against neurotoxicity and oxidative stress caused by Bisphenol A. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[20,[37][38][39] Studies are increasing day by day to reduce these negative effects of BPA. [26,40] GA has important antioxidant, anticancer, anti-inflammatory, and antiapoptotic properties. [41] As the ameliorative effects of GA on BPA-caused cardiotoxicity had not been previously studied, this study demonstrated cardioprotective effects of GA on several antioxidant and antiapoptotic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[20,[37][38][39] Studies are increasing day by day to reduce these negative effects of BPA. [26,40] GA has important antioxidant, anticancer, anti-inflammatory, and antiapoptotic properties. [41] As the ameliorative effects of GA on BPA-caused cardiotoxicity had not been previously studied, this study demonstrated cardioprotective effects of GA on several antioxidant and antiapoptotic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin and rutin Prevention of scopolamine-induced memory impairment [101] Danio rerio Silibinin and Naringenin Prevention of Bisphenol A-induced neurotoxicity [102] As reported in Table 2, most of the studies on 326 the multifaceted effects of bioactive compounds Therefore, the administration of dietary bioactive compounds and/or food and beverage rich in them in transgenic flies and worms allowed the characterization of the multifaceted effects of bioactive compounds on brain plasticity and functionality.…”
Section: Danio Reriomentioning
confidence: 99%
“…Reverse genetics is well established in the zebrafish model for precise exploration of behaviours, such as gene knockdown using antisense morpholino oligos for blocking locations on RNA, or genome-editing technologies like the CRISPR/Cas9 system [1,2]. Humans and zebrafish have been found to have organ-specific structural, physiological and functional features in common, the zebrafish genome has been completely sequenced, and over 80% of human disease-associated genes have been linked to the zebrafish genome [3][4][5]. Using several high-throughput approaches, researchers are now screening a considerable number of compounds for a variety of toxicological endpoints in zebrafish [6].…”
Section: Introductionmentioning
confidence: 99%